2002
DOI: 10.1089/10430340260395910
|View full text |Cite
|
Sign up to set email alerts
|

Development of Catheter-Based Procedures for Transducing the Isolated Rabbit Liver with Plasmid DNA

Abstract: Rapid systemic injection of naked plasmid DNA (pDNA) in a large volume into a mouse tail vein has been shown to result in a high level of gene expression in the liver. However, the potential therapeutic benefit to humans embodied in hydrodynamic transfection of the liver cannot be realized until a clinically viable method for gene delivery is developed. In light of this fact, we have devised and evaluated several methods for delivering pDNA to the isolated rabbit liver using minimally invasive catheter-based t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(96 citation statements)
references
References 32 publications
1
95
0
Order By: Relevance
“…The exact reason for the low gene transfer efficiency of retrograde injection is still unknown, but the low resistance of the sinusoid bed must be a very important factor, as DNA can easily travel across the liver segment after hepatic vein injection, reaching the portal vein and then freely returning to the inferior cava vein through another liver segment. 15 In the present work, we hypothesize that human 'ex vivo' liver segments must be excellent candidates for anadromous gene transfer, as the outflow of injected DNA solution from the targeted segment is blocked in the surgical removal process. In all cases, vascular patency before injection was confirmed by contrast injection and X-ray fluoroscopy.…”
Section: Discussionmentioning
confidence: 92%
“…The exact reason for the low gene transfer efficiency of retrograde injection is still unknown, but the low resistance of the sinusoid bed must be a very important factor, as DNA can easily travel across the liver segment after hepatic vein injection, reaching the portal vein and then freely returning to the inferior cava vein through another liver segment. 15 In the present work, we hypothesize that human 'ex vivo' liver segments must be excellent candidates for anadromous gene transfer, as the outflow of injected DNA solution from the targeted segment is blocked in the surgical removal process. In all cases, vascular patency before injection was confirmed by contrast injection and X-ray fluoroscopy.…”
Section: Discussionmentioning
confidence: 92%
“…[171,176,180] In an attempt to apply this simple procedure of gene delivery to the clinic, efforts have been made to reduce the total injection volume. Eastman et al [181] demonstrated in rabbits that a volume of 15 mL/kg can be safely injected into an isolated rabbit liver. Similar studies have been reported by several groups using pigs as an animal model.…”
Section: Hydrodynamic Gene Delivery (Hydroporation)mentioning
confidence: 99%
“…In vivo study: pigs Initial porcine work aimed to reproduce that of Eastman et al, 8 where in the rabbit model, isolation of the hepatic veins was achieved surgically via the open abdomen. To develop a less invasive technique, presently available balloon catheters were used to isolate the liver.…”
Section: Genetic Constructsmentioning
confidence: 99%
“…Therefore, a method where the rapid fluid shifts were isolated to the liver to minimize the systemic upset was developed in the larger animal model of the rabbit. 8 The technique involved isolation of the inferior vena cava (IVC) at laparotomy and injection of pDNA solution between two balloon catheters within the IVC thereby isolating the liver venous outflow. A number of groups are now modifying this approach to HGT in the pig using balloon catheters to isolate the venous outflow of the liver.…”
Section: Introductionmentioning
confidence: 99%